Morphological Paradigms and the Role of Tense - Pirvulescu, Mihaela (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 2002)
AbstractIn this paper I propose that the existence of morphological paradigms in the domain of the verbal inflection is subject to a morphosyntactic constraint: paradigms are based on an asymmetrical relation between tense and agreement features. The syntactic dependence of agreement features on the Tense node is carried out at the morphological level in the following way: verbal forms that have a syntactic tense representation will be assigned a paradigm in a post syntactic morphological module; verbal forms that do not have a syntactic tense representation will not be assigned a morphological paradigm (as is the case of the so-called non-personal moods like the gerund) or will have a “parasitic paradigm” (as, for example, the subjunctive and the imperative in Romance languages). In other words, tense features legitimate paradigmatic structure. Examples from Romance languages as well as from unrelated languages as Hungarian and Albanian seem to support this hypothesis.